Multi-robot system based on model of wolf hunting behavior to emulate wolf and elk interactions - Madden, J D; Arkin, R C; MacNulty, D R (2010 IEEE International Conference on Robotics and Biomimetics, 2010)
Wolves are one of the most successful large predators on earth. Their success is made apparent by their presence in most northern ecosystems. They owe much of this success to their generalized hunting behavior which allows them to quickly and effectively adjust to different species of prey. The success of this hunting behavior for wolves is the inspiration for a project to bestow this behavior onto a system of robots with the hopes that they might utilize the apparent strengths of the behavior to achieve their own success.